1999
DOI: 10.1002/(sici)1521-4125(199909)22:9<750::aid-ceat750>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrosorption on Activated Carbon Textile

Abstract: 0930-7516/99/0909-00750 $ 17.50+.50/0 Chem. Eng. Technol. 22 (1999) 9 and the means of oxygen transport from the gas-phase into the bulk-phase are questions that still have to be answered in future investigations. ConclusionWithin the bounds of the investigated process-parameters (temperature, pressure, concentration), the application of transient process control is not advantageous to the chosen system:With this simple example we have shown that the introduction of a concentration-programmed-reduction meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In this way, the 34% enhancement of adsorption capacity of activated carbon was observed. The investigations of electrochemically enhanced adsorption for other organics have also been done [19,[25][26][27][28]. The results indicated that polarization of such carbon surfaces in a suitable electrolyte could, to some extent, improve the adsorption of ions and polarizable organic pollutants.…”
Section: Introductionmentioning
confidence: 99%
“…In this way, the 34% enhancement of adsorption capacity of activated carbon was observed. The investigations of electrochemically enhanced adsorption for other organics have also been done [19,[25][26][27][28]. The results indicated that polarization of such carbon surfaces in a suitable electrolyte could, to some extent, improve the adsorption of ions and polarizable organic pollutants.…”
Section: Introductionmentioning
confidence: 99%